A secret gift : how one man's kindness--and a trove of letters--revealed the hidden history of the Great Depression - Gup, Ted. 1950- (New York : Penguin Press, 2010)
The author's grandfather, Sam Stone, placed an ad in the Canton, OH, newspaper shortly before Christmas in 1933, offering cash gifts to seventy-five families in distress. Readers were asked to send letters describing their hardships to a benefactor calling himself Mr. B. Virdot. The author investigates a suitcase full of letters responding to these ads as he learns more about his grandfather's hidden past as well as the suffering and triumphs of strangers during the Great Depression. -- From publisher's description.
A Christmas carol -- In consideration of the white collar man -- The bread of tomorrow -- If I would accept charity -- Families: the crisis that brought them closer -- Families: the crisis that pulled them apart -- An opportunity to help -- A merry and joyful Christmas -- True circumstances.
Includes index.
Keywords: Stone, Samuel, -- 1887-1981.; Benefactors -- Ohio -- Canton -- Biography; Benevolence -- Ohio -- Canton -- History -- 20th century; Canton (Ohio) -- Biography; Canton (Ohio) -- Economic conditions -- 20th century; Canton (Ohio) -- History -- 20th century